Health facility service availability and readiness for intrapartum and immediate postpartum care in Malawi: A cross-sectional survey. - Naoko Kozuki; Lolade Oseni; Angella Mtimuni; Reena Sethi; Tambudzai Rashidi; Fannie Kachale; Barbara Rawlins; Shivam Gupta (PLoS ONE, 2017)
This analysis seeks to identify strengths and gaps in the existing facility capacity for intrapartum and immediate postpartum fetal and neonatal care, using data collected as a part of Malawi's Helping Babies Breath program evaluation. From August to September 2012, the Maternal and Child Health Integrated Program (MCHIP) conducted a cross-sectional survey in 84 Malawian health facilities to capture current health facility service availability and readiness and health worker capacity and practice pertaining to labor, delivery, and immediate postpartum care. The survey collected data on availability of equipment, supplies, and medications, and health worker knowledge and performance scores on intrapartum care simulation and actual management of real clients at a subset of facilities. We ran linear regression models to identify predictors of high simulation performance of routine delivery care and management of asphyxiated newborns across all facilities surveyed. Key supplies for infection prevention and thermal care of the newborn were found to be missing in many of the surveyed facilities. At the health center level, 75% had no clinician trained in basic emergency obstetric care or newborn care and 39% had no midwife trained in the same. We observed that there were no proportional increases in available transport and staff at a facility as catchment population increased. In simulations of management of newborns with breathing problems, health workers were able to complete a median of 10 out of 16 tasks for a full-term birth case scenario and 20 out of 30 tasks for a preterm birth case scenario. Health workers who had more years of experience appeared to perform worse. Our study provides a benchmark and highlights gaps for future evaluations and studies as Malawi continues to make strides in improving facility-based care. Further progress in reducing the burden of neonatal and fetal death in Malawi will be partly predicated on guaranteeing properly equipped and staffed facilities in addition to ensuring the presence of skilled health workers.